DEVELOPMENT OF AQUACULTURE IN THE UKRAINIAN BLACK SEA REGION: ORGANIZATIONAL AND ECONOMIC MEASURES AND NEW APPROACHES - Tiutiunnyk, Hanna (Collection of scientific papers «ΛΌГOΣ», 2024)
The development of aquaculture in the modern world is becoming not only an important aspect of economic growth but also a key factor in ensuring sustainable development, particularly in Ukraine. Legal frameworks and spatial planning play a decisive role in creating favourable conditions for the effective functioning of the aquaculture sector. Ensuring transparency and stability in the business environment through the establishment of appropriate legal frameworks and the implementation of standards in Ukraine is a top priority. Identifying the species composition of aquaculture, regulating aquaculture tourism, and reducing negative environmental impact are important aspects of this process.